Voice and mood a linguistic approach - Mathewson, David 1963- (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2021)
"A recognized expert in Greek grammar examines two features of the Greek verb, voice and mood, in light of modern linguistics and offers fresh insights"--
Includes bibliographical references and indexes
Keywords: Bible -- Language, style; Greek language, Biblical -- Voice; Greek language, Biblical -- Mood